Efektivitas Bahan Edukasi dengan Basis Media Ajar pada Praktik Penyelengaraan Jenazah di Desa Tamalatea Kecamatan Manuju Kabupaten Gowa - Ayyub, Ayyub; Agustina; Musdalifa; Fenny, Risda (AL-IRSYAD AL-NAFS: JURNAL BIMBINGAN DAN PENYULUHAN ISLAM, 2025)
The lack of public understanding of funeral procedures, especially in rural areas, has led to gaps in the implementation of Islamic teachings classified as fardhu kifayah. This study aims to determine the effectiveness of educational media and education conducted in conjunction with funeral practices to measure the increase in public knowledge in Tamalatea Village, Manuju District, Gowa Regency. This study used a quantitative method with a pre-test and post-test design and an observational analytical approach in a cross-sectional form. The research sample consisted of 32 respondents selected through a population approach. Data collection was carried out using a questionnaire instrument and analysed using a paired sample t-test. The results showed an increase in the average knowledge score from 44.06 before education to 48.75 after education. However, the statistical test results showed a p-value of 0.142 (greater than 0.05), indicating that there was no statistically significant difference between the knowledge levels before and after the education programme. Nevertheless, teaching materials have a number of limitations and still have a positive impact on the community’s readiness and skills in conducting funerals, so they can be considered quite effective as a means of improving religious literacy in the community.